2012
DOI: 10.1021/jp209385b
|View full text |Cite
|
Sign up to set email alerts
|

Halide Ion Complexes of Decaborane (B10H14) and Their Derivatives: Noncovalent Charge Transfer Effect on Second-Order Nonlinear Optical Properties

Abstract: Quantum molecular engineering has been performed to determine the second-order nonlinear optical (NLO) properties in different halo complexes of decaborane (B(10)H(14)) and their derivatives using the density functional theory (DFT) method. These decaborane halo complexes of X(-)@B(10)H(14) (X = F, Cl, Br, and I) are found to possess noncovalent charge transfer interactions. The static polarizability (α(0)) and first hyperpolarizability (β(0)) among these complexes increase by moving down the group from F to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…The FF method is broadly applied to investigate NLO because this methodology can be used with the electronic structure method to compute b values. [72][73][74][75][76][77][78][79][80][81] In some very recent reports, b tot calculated by this method was found to be substantiated with the experimental structure-property relationship. 10,82 In the FF method, a molecule is subjected to a static electric eld (F) and the energy (E) of the molecule is expressed as:…”
Section: Computational Methodologysupporting
confidence: 60%
“…The FF method is broadly applied to investigate NLO because this methodology can be used with the electronic structure method to compute b values. [72][73][74][75][76][77][78][79][80][81] In some very recent reports, b tot calculated by this method was found to be substantiated with the experimental structure-property relationship. 10,82 In the FF method, a molecule is subjected to a static electric eld (F) and the energy (E) of the molecule is expressed as:…”
Section: Computational Methodologysupporting
confidence: 60%
“…of the incorporation complex [B 10 H 14 Á Á Á NAl 4 ] À is close to that of X À @B 10 H 14 (X ¼ Cl, Br and I) (1088 a.u.-2859 a.u.) 40 ; but the 0 value 8682 a.u. of the incorporation complex [B 10 H 14 Á Á Á CAl 4 ] 2À is three times larger than that of Cl À @B 10 H 14 (2859 a.u.).…”
Section: Electro-optical Propertiesmentioning
confidence: 98%
“…It had been reported that B3LYP method can provide reasonable agreed geometry structure with experimental values for synthesized I À @B 10 H 14 complex. 40 Further, the more sophisticated second-order Møller-Plesset perturbation (MP2) method with 6-31þG(d) basis set was also used to test the reliability of the B3LYP/6-31þG(d) results for geometries and energies.…”
Section: Computational Detailsmentioning
confidence: 99%
“…These larger off-diagonal components indicate good nonlinear anisotropy, which is a ratio (h) between the off-diagonal and diagonal components. [73][74][75][76] 72 Why is the b amplitude of LALAPM relatively larger than that of urea?…”
Section: Polarizability and Rst Hyperpolarizabilitymentioning
confidence: 99%